A novel artificial bee colony algorithm for solving the supply chain network design under disruption scenarios. (6th June 2013) - Chen, Ting–gui; Ju, Chun–hua
Today, many supply chain design decisions, such as facility location, are strategic in nature and very expensive to change. However, facilities in real world are always vulnerable to partial or complete disruptions. Owing to this reason, we firstly formulate the supply chain network design problem under disruption scenarios as a mixed–integer nonlinear program which maximises the total profit for the whole system. After that, in order to obtain near–optimal solutions with reasonable computational requirements for large problem instances, we have proposed a novel artificial bee colony (ABC) algorithm for solving this problem. Unlike other continuous optimisation problems, the supply chain network design problem under disruption scenarios is a classical discrete NP–hard one. Therefore, the proposed ABC algorithm applies discrete operators to generate new neighbouring food sources for the employed bees, onlookers and scouts. Subsequently, the computational simulations reveal very promising results in terms of the quality of solution.